CALCIUM OXALATE CRYSTALS IN LEAVES OF QUERCUS CERRIS L. AND Q-ILEX L. - Kaplan, Hatice Coelgecen Ayse; Buyukkartal, H Nurhan (BANGLADESH JOURNAL OF BOTANY, 2009)
Leaves of Quercus cerris L. were collected from Zonguldak, Devrek and those of Q. ilex L. samples were collected from Zonguldak, Eregli, Turkey. The leaf sections were subjected to histochemical analysis and brown-black stained calcium oxalate crystals were identified. The organic contents in the leaves were completely cleaned for polarizing microscope investigation. Calcium oxalate crystals were found to be druz and prismatic in Q. cerris and Q. ilex species. While druz crystals were localized in mesophyll, prismatic ones were localized around the leaf vessels. The amount of calcium oxalate crystals per mm(2) was determined in permanent preparations.
Keywords: Calcium oxalate crystals; leaf anatomy; Quercus